(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article provides general information on the effect of the gravitational system on adjacent lines and develops differential equations of adjacent lines, based on which it is possible to reduce the degree of curvature between adjacent line conductors and the length of their parallel positions by reducing the value of the distribution coefficient.